Mucogenic additives for the control of Caligus rogercresseyi in atlantic Salmon (Salmo salar) - Concha, Keila (2017)
Mucus is one of the most important components of fish immunity, it contains components of innate immunity such as glycoproteins, lysozyme, complement proteins, proteolytic enzymes, antimicrobial peptides and immunoglobulins. Current information concerning the generation, physiology and effects of mucus in Atlantic salmon is reviewed, as well as possible mucogenic additives for the control of parasites that may be attractive for future use in the reduction of Caligus rogercresseyi. A full-text multidisciplinary data search was carried out. The topics included in the research process correspond to salmon, mucus, and mucogenic additives. It was found that the additive that generates a greater increase of the mucus components is the probiotic Bacillus sp. The findings suggest that more research is needed to unravel the implications of skin mucosal immunity on fish welfare and diseases of biological importance